The effect of drop jump height on post- activation potentiation as measured by vertical jump performance - Taylor, M.; Thomas, E.; Marszalek, A.; Dohm, H.; Moorman, L. (Research & Investigations in Sports Medicine, 2019)
Post-activation potentiation (PAP) is an enhanced contractile response within the muscles due to prior voluntary activation. The optimal combination of volume, intensity, and rest that results in the greatest performance improvement when using PAP inducing exercises during a warm-up has yet to be determined. Purpose: The purpose of this study was to compare the effects of two different drop jump heights on PAP as measured by subsequent vertical jump performance. Methods: 76 male and female NAIA collegiate athletes (19.9±0.2yrs) completed three different testing session protocols. During the first session, the participants performed a pre-treatment vertical jump test and were familiarized with drop jumps. The second and final testing sessions included five drop jumps with rebound from an 18 or 30-inch box followed by a post-treatment vertical jump test. A repeated measures ANOVA was performed in order to examine differences in vertical jump height attained with no drop jump warm up, an 18-inch drop jump warm up, and a 30-inch drop jump warm up. Result: The mean pre-treatment vertical jump was 58.1±1.8cm while the 18-inch treatment mean was 55.2±1.5cm and the 30-inch treatment mean were 55.6±21.5cm. A repeated-measures ANOVA comparing the vertical jump after the varying drop jump heights showed both treatment conditions to have significantly decreased vertical jump height. Conclusion: Neither of the drop jump treatments were found to significantly improve vertical jump performance when compared to the pre-treatment vertical jump heights.